Sustainability of collaborative networks in higher education research projects: why complexity? Why now?. Issue 7 (3rd July 2018) - Scott, Amanda; Woolcott, Geoff; Keast, Robyn; Chamberlain, Daniel
ABSTRACT: This article outlines the potential of complexity theory as a framework for understanding collaborative project networks and their sustainability within cross-institutional funded projects, responding to funders' interest in projects that deliver public value. Preliminary analysis from an educational project suggests that complexity thinking may be useful also in examining attributes of sustainable networks. The article argues for new measures that shed light on how and why (or why not) collaborative project networks achieve sustainability, removing the current reliance on conventional, linear management and evaluation approaches.